Reconstruction of the Law on Compensation for the Remaining Land Acquisition of Government-Owned Projects in the Perspective of Islamic Law and National Law - Muhammad Rizki Azhari; Akhmad Fauzi Aseri; Muhaimin (Faculty of Law, Universitas Pekalongan, 2025)
Development carried out by the government certainly cannot be separated from the land acquisition process. Legally, land acquisition for development in the public interest is regulated in Law Number 2 of 2012. The government as a policy maker is responsible for the birth of a regulation by looking at it from the perspective of the value of maslahah for the community, especially land owners. Compensation for land acquisition for public interest is one example of a case that can be resolved with this concept, because it is related to worldly matters (muamalah) and social problems. The law in the Qur'an and As - Sunnah teaches to create peace in life with the methods that have been given. The problems raised specifically include what are the weaknesses of the regulation on the period of compensation for the remaining land areas affected by the acquisition of government-owned project land in national law, how is the review of Islamic law related to the weaknesses of the regulation on the period of compensation for the remaining land areas affected by the acquisition of government-owned project land and how is the reconstruction of the law regarding the period of compensation for the remaining land areas affected by the acquisition of government-owned project land from the perspective of Islamic law and national law. The method used in this study is normative legal research through literature studies using a statutory approach ( Statute Approach ), conceptual, case study and comparison. Therefore, in order to obtain legal certainty and achieve a sense of justice, it is necessary to reconstruct several legal provisions regarding the time period for providing compensation for remaining land areas affected by land acquisition for public interest.